Optimization of the environmental compensation fund system for the area: an analysis based on the ISA 2025 draft exploitation regulations - Wang, Yong; Wang, Yiyun; Pan, Xin (Frontiers in Marine Science, 2025)
The latest negotiating text from the International Seabed Authority (ISA) on the Environmental Compensation Fund (ECF) system shows significant progress compared to the provisions in the 2019 Draft Exploitation Regulations. First, the formulation of the ECF rules and procedures has been further elaborated. Second, the scope of application of the ECF has been more precisely delineated. Third, the mechanisms for funding the ECF have been improved. Fourth, the “polluter-pays principle” has been introduced for the first time. Fifth, a periodic review mechanism has also been incorporated for the first time. Nevertheless, the 2025 Draft continues to exhibit certain deficiencies. First, the financial foundations of the ECF remain unreliable. Several new or modified sources of funding, such as voluntary contributions from member States, targeted contributions from sponsoring States, and donations from international or non-governmental organizations, are inherently uncertain. Second, the text fails to establish clear and operational criteria for determining eligibility to submit claims to the ECF. Third, the scope of compensation available under the ECF remains inadequately defined. Fourth, transparency for stakeholders with respect to the operation of the ECF is insufficient. This study proposes the following recommendations to deal with the abovementioned deficiencies. First, the principles, mechanisms, and specific measures for the ECF fundraising and management should be optimized. Second, with respect to eligible claimants, a multi-tiered and sequential framework is recommended. Third, the scope of the ECF’s compensatory mandate should be refined, and detailed standards developed to ensure that the ECF is used exclusively to address liability gaps where environmental harm cannot otherwise be remedied. Fourth, stakeholder transparency must be enhanced.